Metode Pembelajaran Mendongeng Sebagai Upaya Meningkatkan Kemampuan Sosial-Emosional Anak Usia Dini TK Islam Insan Mulia Mojokerto - Wahono; Naili Sa'ida; Nursalina Laela (J-SES : Journal of Science, Education and Studies, 2023)
The aim of this research is to determine the application of storytelling learning methods as an effort to improve the social-emotional abilities of early childhood children at the Insan Mulia Mojokerto Islamic Kindergarten. Children need to be given stimulation to improve their social-emotional abilities from an early age because this is one of the efforts to educate the nation's children. This research is quantitative research with a descriptive and inferential approach. The population in this study is the Insan Mulia Mojokerto Islamic Kindergarten. Sampling was taken using a purposive sampling method with the aim of obtaining a representative sample. Data collection techniques were carried out by distributing pretests and posttests to students before and after learning. The research method used to test the hypothesis in this research is using the multiple linear regression analysis method, using SPSS software. 16.00 for windows. So the research results show that according to the output of the Paired Samples Test, it is known that the significance value of Sig. (2-tailed) is 0.000 < 0.05, then H0 is rejected and Ha is accepted, so it can be concluded that there is an average difference between pretest and posttest learning outcomes, which means there is an influence of the application of storytelling learning methods as an effort to improve social skills. -emotional early childhood in Insan Mulia Mojokerto Islamic Kindergarten. So in this way it can also be seen that the calculated t has a negative value of -15,289. This t-count has a negative value because the average pretest learning score is lower than the average posttest learning result so that the t-count becomes t-count -33.140 > t-table 2.145, which means that the basis for decision making is that H0 is rejected and Ha accepted.